2015
DOI: 10.1038/eye.2015.216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telephone consent and potential for eye donation in the UK: the Newcastle Eye Centre study

Abstract: Aims To examine the impact of telephone consent introduced in 2007 on the eye donation rate and to report the changing trend and potential for improvement in eye donation in Newcastle upon Tyne, UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In this study, 68.50% of the students were aware that prior permission before death is necessary for eye donation. In a study conducted by Ting et al (2016), it was found that consent over the telephone has been much more useful than getting consent face to face. If consent can be obtained from the family over a phone call, it will be a signi icant move in increasing the eye donation rates as it simpli ies the process.…”
Section: Knowledge Regarding Other Donor-related Queriesmentioning
confidence: 99%
“…In this study, 68.50% of the students were aware that prior permission before death is necessary for eye donation. In a study conducted by Ting et al (2016), it was found that consent over the telephone has been much more useful than getting consent face to face. If consent can be obtained from the family over a phone call, it will be a signi icant move in increasing the eye donation rates as it simpli ies the process.…”
Section: Knowledge Regarding Other Donor-related Queriesmentioning
confidence: 99%
“…Hospitals within Newcastle upon Tyne The process of eye donation and retrieval in our region has been described previously. 2 Briefly, all deaths in hospitals within Newcastle upon Tyne were identified by two full-time eye donation specialist nurses (JP and TL). They were trained by the NHSBT to identify potential eye donors, to examine medical records for medical contraindications, to approach and obtain consent for eye donation from relatives, and to retrieve eyes from suitable donors.…”
Section: Process Of Eye Donation and Retrievalmentioning
confidence: 99%
“…We recently reported the success of this initiative, which demonstrated an 88% increase in eye donation when telephone consent was used in addition to the conventional face-to-face interview. 2 Nonetheless, merely increasing the eye donation rate is not sufficient. A successful corneal transplant relies on a series of welldefined steps in the donation-transplantation pathway, starting with identification and referral of potential donors, approaching the relatives of these potential donors to obtain consent for eye donation, eye retrieval, transport of the eyes to the eye bank for processing and corneal storage, donor testing for markers of transmissible disease, and investigation of the donor's medical history to exclude corneas from donors with medical contraindications to transplantation, quality assessment (eg, based on endothelial cell density) of corneas, and ultimately transplanting the donated corneas.…”
Section: Introductionmentioning
confidence: 99%
“…13 To address the constant deficit of donor corneas, various countries have considered and implemented a range of initiatives and research programmes, including campaigns to increase public awareness of corneal donation, introduction of telephone consent, refinement in the eye retrieval and eye banking systems, and development of corneal cell-based therapy. 14-18…”
Section: Introductionmentioning
confidence: 99%